Enhancing Ecosystem Resilience: Integrated Forest Rehabilitation in River Watershed Areas for Sustainable Development - Rafina; Sandri; Halifah (Cebong Journal, 2024)
This research examines the intricacies of forest and critical land rehabilitation planning within river watershed areas. Through a multidisciplinary approach integrating ecological assessments, socio-economic analysis, and stakeholder engagement, the study aims to evaluate the effectiveness of existing rehabilitation efforts and propose strategies for enhancing ecosystem resilience, biodiversity conservation, and sustainable development. The analysis reveals significant patterns of forest degradation, critical land erosion, and habitat loss within river watershed areas, driven by socio-economic factors, unsustainable land use practices, and institutional constraints. Despite these challenges, existing rehabilitation efforts have shown promising outcomes in terms of ecosystem health improvement, water quality enhancement, and socio-economic benefits to local communities. Moving forward, addressing these challenges requires integrated approaches that prioritize ecosystem-based solutions, stakeholder collaboration, and adaptive management strategies. Policy integration and coherence between forest and watershed management sectors are essential for promoting synergies and maximizing co-benefits across different policy domains. Moreover, targeted conservation strategies, sustainable land use practices, and governance mechanisms are critical for addressing socio-economic drivers of degradation and promoting inclusive decision-making processes.